Hip arthroplasty as a chance for a normal life - Kwiatkowska, Małgorzata Maria; Skierkowska, Natalia; Topka, Weronika; Prylińska, Monika; Gajos, Wiktoria (Journal of Education, Health and Sport, 2020)
The aim of the study is to review and analyze the medical literature on hip arthroplasty. Hip arthroplasty is a popular procedure in orthopedics nowadays. Implantation of an artificial joint allows the patient to return to work, practice hobbies or sportsand most importantly have a pain free life. The paper describes the theoretical basis of hip arthroplasty, types of procedures used in orthopedics in this field, the most important contraindications and the importance of physiotherapeutic treatment. The treatment, combined with well and individually planned pre- and postoperative rehabilitation, can bring spectacular results. The postoperative rehabilitation program is selected individually. It should be noted that every patient is different, therefore the improvement plan sometimes has to be reviewed on an ongoing basis during its implementation. The main goals of rehabilitation after artificial joint implantation are: to reduce pain, increase the range of motion of the operated joint and strengthen the muscles of the entire body.